2015
DOI: 10.1158/2159-8290.cd-15-0060
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and Overriding the Structural Mechanism of the Quizartinib-Resistant FLT3 “Gatekeeper” F691L Mutation with PLX3397

Abstract: Tyrosine kinase domain mutations are a common cause of acquired clinical resistance to tyrosine kinase inhibitors (TKIs) used to treat cancer, including the FLT3 inhibitor quizartinib. Mutation of kinase “gatekeeper” residues, which control access to an allosteric pocket adjacent to the ATP-binding site, have been frequently implicated in TKI resistance. The molecular underpinnings of gatekeeper mutation-mediated resistance are incompletely understood. We report the first co-crystal structure of FLT3 with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
140
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(149 citation statements)
references
References 29 publications
(49 reference statements)
4
140
0
Order By: Relevance
“…15 Moreover, our findings emphasize the importance of careful characterization of genetically modified mice before drawing conclusions about the pathologies they model, particularly when targeted therapeutic interventions are being investigated. Although the genetic variant influencing drug response was not present in wild-type mice in our study, in other cases it may represent a consistent human -mouse difference, as was recently described for lenalidomide and a mousespecific variant in Cereblon (Crbn) that makes murine cells insusceptible to the drug.…”
Section: Itd/+mentioning
confidence: 80%
See 1 more Smart Citation
“…15 Moreover, our findings emphasize the importance of careful characterization of genetically modified mice before drawing conclusions about the pathologies they model, particularly when targeted therapeutic interventions are being investigated. Although the genetic variant influencing drug response was not present in wild-type mice in our study, in other cases it may represent a consistent human -mouse difference, as was recently described for lenalidomide and a mousespecific variant in Cereblon (Crbn) that makes murine cells insusceptible to the drug.…”
Section: Itd/+mentioning
confidence: 80%
“…As the murine F692L variant is equivalent to the human F691L gatekeeper mutation, which confers AML resistance to multiple FLT3 tyrosine kinase inhibitors, 3,15 we proceeded to test whether this was also true for the murine variant. To do this we cultured AML cells from two independent Npm1 cA/+ ; Flt3…”
mentioning
confidence: 99%
“…One important example is quizartinib (also known as AC220), a very potent and selective Flt3 inhibitor that was among the first to show efficacy as a single agent against Flt3-ITD + AML 5,31 . Quizartinib often induces rapid remission in Flt3-ITD + AML, but acquired drug resistance, commonly in the form of Flt3 kinase domain mutations, has limited its effectiveness 4,5,3234 . Unlike TL02–59, we found that quizartinib does not inhibit Fgr or other AML-associated kinases, including Syk, Fes, or Hck in vitro; the same is true for other Flt3 inhibitors tested in the clinic, including sorafenib, sunitinib, and tandutinib (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Although the findings validated that the mechanism of response to quizartinib was due to FLT3 inhibition, they also pointed to a need to develop drugs that target both FLT3-ITD and common TKD resistance mutations as a method to circumvent resistance and maximize the efficacy of FLT3 inhibition. 13,14 Two such agents quickly followed, each showing in vitro activity against both FLT3-ITD and FLT3-D835, the most common TKD mutation conferring resistance to quizartinib. First to enter trials was crenolanib, which was quickly followed by gilteritinib (ASP2215).…”
Section: Mutation Targeted Agents: Flt3 Inhibitorsmentioning
confidence: 99%